2016
DOI: 10.1016/j.jadohealth.2016.04.008
|View full text |Cite
|
Sign up to set email alerts
|

A Depression Prevention Intervention for Adolescents in the Emergency Department

Abstract: PURPOSE To evaluate acceptability and feasibility of a theoretically-based two-part (brief in-person + eight-week automated text-message) depression prevention program, “iDOVE”, for high-risk adolescents. METHODS English speaking emergency department (ED) patients (age 13–17, any chief complaint) were sequentially approached for consent on a convenience sample of shifts, and screened for inclusion based on current depressive symptoms & past year violence. After consent, baseline assessments were obtained; al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 35 publications
1
59
0
2
Order By: Relevance
“…Recent literature suggests that pushing noninteractive messages to older teens with repetitive information or too often might cause disinterest [15]. The future of texting interventions may lie with innovative, bidirectional, tailored messaging, which changes behavior by creating an automated yet engaging conversation [4,5,7]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent literature suggests that pushing noninteractive messages to older teens with repetitive information or too often might cause disinterest [15]. The future of texting interventions may lie with innovative, bidirectional, tailored messaging, which changes behavior by creating an automated yet engaging conversation [4,5,7]. …”
Section: Discussionmentioning
confidence: 99%
“…Text messaging (TM) has the potential to lead to behavior change, although little data from patients in the ED exist [47]. Our objective was to determine the feasibility and acceptability of an ED-based texting intervention to increase contraception initiation among adolescent females at high risk of pregnancy.…”
mentioning
confidence: 99%
“…Most interventions delivered through text messaging to youth in clinical populations have not harnessed the potential of the medium for interactive communication, instead using one-way messaging or reminders to reinforce behaviors and direct the attention of participants towards core intervention concepts. One exception to this trend is the iDOVE program [18,19] which made limited use of interactivity, providing CBT coaching to adolescents with depressive symptoms who presented in a general emergency department. In response to automated daily prompts, participants could receive a single automated daily message, or could initiate the receipt of a single additional support message if they were feeling sad, angry, or stressed.…”
Section: Pmentioning
confidence: 99%
“…A pilot test of an automated text-based intervention for adolescents who screened positive for depression and past-year violence in an emergency department was well-received by patients and promising in terms of symptom improvement [18,19]. Few texting interventions aimed at youth in the general population (outside of clinical contexts) have been tested for efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study, involving adolescents attending emergency department at risk of depression, has shown that brief in-person discussion in the emergency, followed by 8-week automated messaging intervention is feasible and acceptable [65]. Telephone calls has also been used to deliver these interventions for older patients unable to attend the clinic due to pain [58].…”
Section: Text Messaging Intervention Programmentioning
confidence: 99%